Music in the community : a study of community music projects in the Western Cape, with specific reference to the Redefine Music Education Project, in Kuils River. - Le Roux, Babette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MMus (Music))--University of Stellenbosch, 2009.